Membrane stabilization of biodegradable polymersomes - Katz, Joshua S (Langmuir : the ACS journal of surfaces and colloids, 2009)
Biodegradable polymersomes are promising vehicles for a range of applications. Their stabilization would improve many properties, including the retention and controlled release of polymersome contents, yet this has not been previously accomplished. Here, we present the first example of stabilizing fully biodegradable polymersomes through acrylation of the hydrophobic terminal end of polymersome-forming poly(caprolactone-b-ethylene glycol). Exposure of the resulting polymersomes loaded with a hydrophobic photoinitiator to ultraviolet light polymerized the acrylates, without affecting polymersome morphology or cell cytotoxicity. These stabilized polymersomes were more resistant to surfactant disruption and degradation. As an example of stabilized polymersome utility, the unintended release of doxorubicin (DOX) due to leakage from polymersomes decreased with membrane stabilization and slower sustained release was observed. Finally, DOX-loaded polymersomes retained their cytotoxicity following stabilization